A study of convenience store attributes in influencing customers’ patronage intention / Nuranisah Nizar - Nizar, Nuranisah (2016)
This study aims to study on the convenience store attributes in influencing consumers’ patronage intention specifically at petrol station. 5 Service Convenience elements such as Access Convenience, Decision Convenience, Benefit Convenience, Transaction Convenience and Post Benefit Convenience were used to measure consumers’ patronage intention in this study. The researcher was interested to identify what are the most factors that influence consumers’ to shop at convenience store. In order to get the information from customers, the researcher had distributed questionnaires randomly to 100 respondents by using questionnaire and online questionnaire. The online questionnaires were distributed through whatsapp mobile application and also email. Then, the researcher further analyzed all the data by using Statistical Package for Social Science (SPSS) computer software. All the data were interpreted in this study. Therefore, there are several recommendations or suggestions were developed and provided to the company not specifically PETRONAS only, but also to other petrol station companies that have convenience store attached to it. The recommendations can help the company to know which store attributes that can directly or indirectly influence consumers’ patronage intention toward the convenience store. By this, it helps company to identify the areas of improvement thus can increase its sales